MANAJEMEN PEMASARAN LEMBAGA PENDIDIKAN TINGGI DALAM PENERIMAAN MAHASISWA BARU DI UNIVERSITAS ISLAM LAMONGAN - Razaq, Mohammad Fahmi; Roesminingsih, Maria Veronika; Hariastuti, Retno Tri (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Competition in college became inevitable in modern times. In an effort to meet the community's need for further education, several universities compete with each other to get new students. Therefore, universities must use effective marketing management. This study aims to analyze the marketing management of Lamongan Islamic University in maintaining competition by increasing the amount of students from year to year. The results of this study include: (1) implementing marketing management measures through market identification, market segmentation, and product differentiation. (2) in the application of marketing, it is carried out in two ways, namely internal marketing and external marketing. (3) the obstacles faced in the implementation of marketing are the presence of state universities that are starting to enter the region and there are competitors who use similar marketing strategies, thus influencing prospective students in choosing the services to be selected. The results of this study are the marketing of educational services in higher education is very influential in an effort to increase the number of students. With marketing activities in educational services, prospective students can find out information about the products and services offered, so that prospective students can make decisions about choosing a place to study.